Urgensi Penegakan Hukum Pada Lembaga Keuangan Koperasi Dalam Rangka Perlindungan Hukum Terhadap Anggota - I Gusti Agung Wisudawan (Jatiswara, 2015)
One of the goals of the Cooperative is for the welfare of its members based on the principle of kinship and mutual cooperation, so that the management is required to apply the standard of professional management and responsible as to uphold the principles of transparency, accountability, independence and accountability both legally and economically and democratically. Cooperative as a pillar of the economy of the Indonesian nation must make its contribution to improving the economy of the community. Several cases that emerged recently as in the case of fraud by unscrupulous members of the cooperative board, the credit agreement that violates the rules so as to make the cooperative becomes a loss, lack of monitoring and evaluation internally by the cooperative supervisors. It would be a black mark to the development of cooperatives in Indonesia, so that the necessary urgency enforcement seriously and comprehensively both by the Ministry and the Department of Cooperatives and SMEs as well as elements of other law enforcement in order to restore the good name of the cooperative in the community as one of the pillars of the economy-based society.